2018
DOI: 10.1038/s41419-018-1215-4
|View full text |Cite
|
Sign up to set email alerts
|

UBIAD1 suppresses the proliferation of bladder carcinoma cells by regulating H-Ras intracellular trafficking via interaction with the C-terminal domain of H-Ras

Abstract: UbiA prenyltransferase domain-containing protein 1 (UBIAD1) plays a key role in biosynthesis of vitamin K2 and coenzyme Q10 using geranylgeranyl diphosphate (GGPP). However, the mechanism by which UBIAD1 participates in tumorigenesis remains unknown. This study show that UBIAD1 interacts with H-Ras, retains H-Ras in the Golgi apparatus, prevents H-Ras trafficking from the Golgi apparatus to the plasma membrane, blocks the aberrant activation of Ras/MAPK signaling, and inhibits the proliferation of bladder canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
(117 reference statements)
0
12
0
Order By: Relevance
“…To investigate the essential role of ER stress in HIPK2-mediated cytokine production, TM, an ER stress agonist ( 14 ), was used to establish the effects of HIPK2 knockdown in macrophages. The results revealed that while HIPK2 knockdown attenuated IL-6 and TNF-α production, the application of TM, though slightly decreased IL-6 and TNF-α compared with the control, abolished the attenuation of cytokine production ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the essential role of ER stress in HIPK2-mediated cytokine production, TM, an ER stress agonist ( 14 ), was used to establish the effects of HIPK2 knockdown in macrophages. The results revealed that while HIPK2 knockdown attenuated IL-6 and TNF-α production, the application of TM, though slightly decreased IL-6 and TNF-α compared with the control, abolished the attenuation of cytokine production ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed UBIAD1 is a target of onco-microRNA miR-4644 in bladder cancer 34 . UBIAD1 could inhibit the proliferation of bladder cancer cells via interaction with H-Ras 35 . TJP2 encodes protein functions as a component of the tight junction barrier in epithelial and endothelial cells and is necessary for proper assembly of tight junctions 36 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, members of the RASSF family promote Ras-induced apoptosis and senescence and oppose Ras-induced mitogenic and survival signaling [ 72 ]. It should also be noted that other proteins are involved in Ras signaling regulation, such as UBIAD1, which interacts with the C-terminal region of HRas and modulates its trafficking from the Golgi apparatus to the plasma membrane [ 73 ] or the prenyl-binding protein PDEδ, regulating the correct localization and signaling by farnesylated KRas [ 74 ]. The crosstalk and relative balance between all these pathways determine the cellular responses, which require a system level approach to be understood.…”
Section: Ras Signaling In Mammalian Cellsmentioning
confidence: 99%
“…Bound nucleotides (GDP or GTP) are associated with dynamic conformational changes in the effector lobe, which contains the two regions of Ras known as switch I (residues [30][31][32][33][34][35][36][37][38] and switch II (residues [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. Together with the phosphate-binding motif (P-loop, residues 10-17), switch I constitutes the nucleotide binding pocket, while switch II is the flexible region that undergoes the main conformational changes upon nucleotide exchange [6].…”
Section: Ras Proteinsmentioning
confidence: 99%
See 1 more Smart Citation